Lecture 3

# In particular c a z for all z c since c is a cone it

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: co C )∗ , and (iii) C ∗ ⊃ D∗ . Proof. C ∗ is nonempty since 0 ∈ C . Since the half space − Hx := y ∈ RN ⟨x, y ⟩ ≤ 0 − is a closed convex cone (easy), so is C ∗ = x∈C Hx . If y ∈ D∗ , then ⟨x, y ⟩ ≤ 0 for all x ∈ D. Since C ⊂ D, we have ⟨x, y ⟩ ≤ 0 for all x ∈ C . Therefore y ∈ C ∗ , which proves D∗ ⊂ C ∗ . Finally, since C ⊂ co C , we have C ∗ ⊃ (co C )∗ . To prove the reverse inclusion, take any x ∈ co C . By Lemma 1, there exists a K convex combination x = k=1 αk xk such that xk ∈ C for all k . If y ∈ C ∗ , it follows that ⟨x, y ⟩ = αk xk , y = αk ⟨xk , y ⟩ ≤ 0, so y ∈ (co C )∗ . Therefore C ∗ ⊂ (co C )∗ . Proposition 6. Let C ⊂ RN be a nonempty cone. Then C ∗∗ = cl co C . (C ∗∗ is the dual cone of C ∗ , so it is the dual cone of the dual cone of C .) Proof. Let x ∈ co C . For any y ∈ C ∗ = (co C )∗ we have ⟨x, y ⟩ ≤ 0. This implies x ∈ C ∗∗ . Hence co C ⊂ C ∗∗ . Since the dual cone is closed, we have cl co C ⊂ cl C ∗∗ = C ∗∗ . To show the reverse inclusion, suppose that x ∈ cl co C . Then by Proposition / 4 there exists a separating hyperplane such that ⟨a, x⟩ > c > ⟨a, z ⟩ 2014W Econ 172B Operations Research (B) Alexis Akira Toda for any z ∈ co C . In particular, c > ⟨a, z ⟩ for all z ∈ C . Since C is a cone, it must be ⟨a, z ⟩ ≤ 0 for all z , for otherwise if there is z0 ∈ C with ⟨a, z0 ⟩ > 0, for any β > 0 we have β z0 ∈ C , but for large enough β we have ⟨a, β z0 ⟩ = β ⟨a, z0 ⟩ > c, a contradiction. This shows that a ∈ C ∗ . Again since C is a cone, we have 0 ∈ C , so c > ⟨a, 0⟩ = 0. Since ⟨a, x⟩ > c >= and a ∈ C ∗ , it follows that x ∈ C ∗∗ . Therefore C ∗∗ ⊂ cl co C . / The following corollary will play an important role in optimization theory. Corollary 7 (Farkas). Let C = cone[a1 , . . . , aK ] be a polyhedral cone generated by a1 , . . . , aK . Let D = y ∈ RN (∀k ) ⟨ak , y ⟩ ≤ 0 . Then D = C ∗ and C = D∗ . Proof. Let y ∈ D. For any x ∈ C , we can take {αk } ≥ 0 such that x = Then ⟨x, y ⟩ = αk ⟨ak , y ⟩ ≤ 0, k αk ak . k so y ∈ C . Conversely, let y ∈ C . Since ak ∈ C , we get ⟨ak , y ⟩ ≤ 0 for all k , so y ∈ D. Therefore D = C ∗ . Since C is a closed convex cone, by Propositions 6 and 5 (iii) we get ∗ ∗ C = cl co C = C ∗∗ = (C ∗ )∗ = D∗ . 4 4.1 Applications to economics and ﬁnance Pareto eﬃcient allocations Suppose that there are I consumers indexed by i = 1, . . . , I with continuous utility functions ui : RN...
View Full Document

## This document was uploaded on 02/18/2014 for the course ECON 172b at UCSD.

Ask a homework question - tutors are online